AKIBAT HUKUM WANPRESTASI PADA KASUS PEMBATALAN KONSER MUSIK - Hardian Iskandar (Universitas Muhammadiyah Gresik, 2019)
Due to legal defaults at music concerts result in: First paying for losses that have been experienced by one of the parties. Second, it can result in the cancellation of the agreed agreement. Third, there is a risk transfer and Fourth, paying the case for the case filed before the judge (court). The form of payment intended in this case is the return of tickets by the parties / organizers of music concerts.Costs are any money (including costs) that must be incurred in real terms by the injured party, in this case as a result of default. Whereas the term